Respuesta :
Answer:
The standard form of the given expression is y = -6x - 40.
Step-by-step explanation:
Here , the given expression is y +4= -6(x + 6)
The above equation represents the line of an equation.
It of the POINT SLOPE FORM : y - y0 = m (x -x0)
Now, the standard form of a line Equation is SLOPE INTERCEPT form:
y = m x + C
Simplifying the given expression, we get,
y +4= -6(x + 6) ⇒ y + 4 = -6x - 36
or, y = -6x - 36 -4
or, y = -6x - 40
It is of the SLOPE INTERCEPT form.
Hence, the standard form of the given expression is y = -6 x - 40.
Answer:
6x+y=−40
Step-by-step explanation:
I got it on Khan Academy